Multifaceted roles of zinc finger proteins in regulating various agronomic traits in rice - Huang, Yifeng; Du, Longgang; Wang, Meixi; Ren, Mengyun; Yu, Shouwu; Yang, Qianying (Frontiers in Plant Science, 2022)
Rice is an important cereal crop, which provides staple food for more than half of the world's population. To meet the demand of the ever-growing population in the next few decades, an extra increase in rice yield is an urgent need. Given that various agronomic traits contribute to the yield of rice, deciphering the key regulators involved in multiple agronomic trait formation is particularly important. As a superfamily of transcription factors, zinc finger proteins participate in regulating multiple genes in almost every stage of rice growth and development. Therefore, understanding zinc finger proteins underlying regulatory network would provide insights into the regulation of agronomic traits in rice. To this end, we intend to summarize the current advances in zinc finger proteins, with emphasis on C2H2 and CCCH proteins, and then discuss their potential in improving rice yield.